Social Fairness in a Post-Pandemic World Interdisciplinary Perspectives - Ishido, Hikari; Mizushima, Jiro; Kobayashi, Masaya; Zhang, Xiaofang (Springer Nature Singapore : Imprint: Palgrave Macmillan, 2023)
XXII, 270 p. 41 illus.